Tinjauan Hukum Islam dan Hukum Positif Terhadap Praktik Jual Beli Sistem Dropshipping - Dede Maulana Yusuf; Aturkian Laia (INDO PUBLISHING, 2026)
The dropshipping system as a rapidly growing digital business model in Indonesia presents complex legal issues, both in terms of sharia compliance and national legal certainty. This research examines dropshipping practices from Islamic law and Indonesian positive law perspectives, focusing on legality, regulation, and harmonization between the two legal systems. Using a descriptive-analytical and comparative normative juridical approach, this research examines DSN-MUI fatwas, laws and regulations, and related academic studies. The findings indicate that in Islamic law, dropshipping is debated because it conflicts with the prohibition of selling goods not yet owned, but DSN-MUI Fatwa Number 145/DSN-MUI/XII/2021 provides a solution through wakalah bil ujrah or salam contracts with the condition of no fraud. Positive law recognizes dropshipping as a legitimate business activity, yet no comprehensive regulation exists, creating uncertainty in legal responsibility and tax compliance. Harmonization between the two laws finds common ground in consumer protection and fraud prohibition, yet still faces challenges in goods specification clarity and sharia principle integration. This research recommends updating the KHES and drafting specific regulations integrating sharia principles and positive law.